2005
DOI: 10.2135/cropsci2004.0406
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Resistance Genes for the Rice Gall Midge in Two Rice Genotypes

Abstract: spect to specific host plant resistance genes (Gallun et al., 1961). Asian rice gall midge (Orseolia oryzae Wood-Mason) is the mostNine nonallelic resistant genes were identified in indestructive pest of rice (Oryza sativa L.) in several regions of South heritance studies of gall midge resistance using approxiand Southeast Asia. Resistance to gall midge is primarily governed mately 100 different rice lines as donors. The Gm1 (gall by single dominant genes in rice, thus newly evolving biotypes are able to overc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…A simple test to detect the presence of Gm1 and Gm2 in the large pool of gall midge resistant genotypes will greatly reduce the effort required to identify new genes. Random selection of genotypes and classical allelic tests have led to the characterization of 10 resistance genes so far (Kumar et al 2005). None of these genes confers resistance against all the known gall midge biotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A simple test to detect the presence of Gm1 and Gm2 in the large pool of gall midge resistant genotypes will greatly reduce the effort required to identify new genes. Random selection of genotypes and classical allelic tests have led to the characterization of 10 resistance genes so far (Kumar et al 2005). None of these genes confers resistance against all the known gall midge biotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Field and greenhouse evaluation of about 50,000 germplasm accessions has resulted in the identification of over 300 primary sources of resistance . Genetic analysis in some of these sources led to the characterization of nine dominant genes and one recessive gene conferring resistance (Kumar et al 2005). Utilizing 4-5 of these sources of resistance, over 60 gall midge resistant rice varieties have been developed and released for commercial cultivation in India since 1972 .…”
Section: Introductionmentioning
confidence: 99%
“…However, for polymorphism analysis biotypes GMB1, GMB4 and GMB4M were used. The rice ( Oryzae sativa ) cultivars used for rearing the insects were Jaya (susceptible to GMB4) and RP2068 (resistant to GMB4) (Bentur et al ., ; Kumar et al ., ). GMB4 infestation on rice cultivar Jaya leads to the formation of a gall chamber, whereas on cultivar RP2068, a hypersensitive‐mediated (HR + ) defence response is initiated and the insects succumb to the plant defence response within 96 h of egg hatching.…”
Section: Methodsmentioning
confidence: 97%
“…Use of resistant varieties has been the most feasible alternative to manage the pest. Ample sources of resistance are available in cultivated rice, Oryza sativa L. Inheritance studies have identified nine dominant and one recessive gene imparting resistance to different biotypes of Asian rice gall midge (Kumar et al 2005;Pani and Sahu 2000), and eight of them have been tagged with different molecular markers. Mohan et al(1994) identfied two RFLP markers, RG329 and RG476, linked to the gall midge resistance gene, Gm2 in the rice cv.…”
Section: Introductionmentioning
confidence: 99%